2011
DOI: 10.1097/pas.0b013e318206b67b
|View full text |Cite
|
Sign up to set email alerts
|

ERG Transcription Factor as an Immunohistochemical Marker for Vascular Endothelial Tumors and Prostatic Carcinoma

Abstract: ERG, an ETS family transcription factor, is known to be expressed in endothelial cells, and oncogenic ERG gene fusions occur in subsets of prostatic carcinoma, acute myeloid leukemia, and Ewing sarcoma. In this study, we immunohistochemically investigated nuclear ERG expression using a new monoclonal antibody, CPDR ERG-MAb, that is highly specific for detecting ERG protein and ERG-expressing prostate carcinomas. A broad range of vascular endothelial (n = 250), other mesenchymal (n = 973), and epithelial tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
248
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(260 citation statements)
references
References 29 publications
(42 reference statements)
7
248
2
3
Order By: Relevance
“…Of note, angiomatoid and cutaneous fibrous histiocytoma both did not exhibit ERG immunoreactivity. 24 In summary, by demonstrating a broad applicability of both, the rabbit and mouse ERG-MAb, we confirm the feasibilty of ERG IHC in PCa. Given the comfort of performing IHC versus FISH, ERG protein-based stratification of PCa in formalin-fixed paraffinembedded tissue and in decalcified material may evolve into a valuable tool for routine diagnostics.…”
Section: Discussionsupporting
confidence: 67%
“…Of note, angiomatoid and cutaneous fibrous histiocytoma both did not exhibit ERG immunoreactivity. 24 In summary, by demonstrating a broad applicability of both, the rabbit and mouse ERG-MAb, we confirm the feasibilty of ERG IHC in PCa. Given the comfort of performing IHC versus FISH, ERG protein-based stratification of PCa in formalin-fixed paraffinembedded tissue and in decalcified material may evolve into a valuable tool for routine diagnostics.…”
Section: Discussionsupporting
confidence: 67%
“…[23][24][25][26] Given differences in sensitivity and specificity, a panel of antibodies should be used. [23][24][25] Some angiosarcomas co-express epithelial antigens (EMA, Cam5.2 and AE1/3), a fact that should be considered in distinguishing them from carcinoma.…”
Section: Pathological Featuresmentioning
confidence: 99%
“…Chimeric variants with other Ets family members can exist, and the same tumor can even harbor multiple fusion variants. [9][10][11][12][13] Translocations and deletions of ERG are also seen in some acute myeloid leukemias and ERG overexpression has been associated with poor prognosis. 14,15 In addition, ERG is involved in the development of both hematopoietic and endothelial cells.…”
mentioning
confidence: 99%
“…[18][19][20] Several studies have shown anti-ERG antibody useful for prostate carcinoma, metastatic and primary, and prostatic intraepithelial neoplasias. [10][11][12]21,22 The detection of ERG is highly correlated with both ERG rearrangement by fluorescence in-situ hybridization and with ERG mRNA overexpression. 10,12,21 Similar to FLI1, ERG is also found to be expressed in both benign and malignant vascular tumors serving as a helpful marker for endothelial differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation